Occupational Stress, Personality Traits and Job Jatisfaction. the Case of Pakistani Police Officers - Khizar, Umbreen; Mustafa, Jamaludin; c.Orcullo, Daisy jane (International Journal of Engineering and Technology, 2018)
The intend of this study is to measure the personality traits (Conscientiousness, Extraversion, Openness to experience, Neuroticism and Agreeableness) and occupational stress in correlation with job satisfaction of police officers. Respondents were 300 senior police officers from Punjab, Pakistan. Job Satisfaction Survey (JSS), Police Stress Questionnaire (PSQ) and Neo Five Factor Inventory (NEO-FFI) were used as research instruments. It was concluded thatÂ  conscientiousness, extraversion and agreeableness personality traits have positive relationship with job satisfaction and neuroticism is negatively correlated. No correlation was found of openness to experience with job satisfaction. Negative correlation was concluded between occupational stress and job satisfaction.